Analyze of students’ mathematical disposition and learning independence through blended learning: A study in West Sumatra, Indonesia - Yulia, Yulia; Kustati, Martin; Afriadi, Juli (Universitas Islam Raden Intan Lampung, INDONESIA, 2024)
Background: In recent years, there has been a growing emphasis on fostering students' mathematical disposition and promoting learning independence in mathematics education.Aim: This study aims to determine the relationship between mathematical disposition and learning independence of Mathematics Education students in West Sumatra.Method: This research employs a descriptive correlational design utilizing a survey method. The population consists of all Mathematics Education students enrolled in the academic year 2022, with a sample size of 291 students selected through purposive sampling. Data analysis techniques include simple linear regression analysis and Pearson correlation.Results: The regression analysis revealed a positive influence of mathematical dispositions (X) on learning independence (Y) with a regression coefficient (b) of 2.15 and a significance level of 0.067. The correlation coefficient (r) was found to be 0.73, indicating a strong linear relationship between X and Y.Conclusion: The study concludes that there is a positive relationship between mathematical disposition and the learning independence of Mathematics Education students in West Sumatra. Higher levels of mathematical disposition are associated with greater learning independence.